The Long-Term Impact of High School Financial Education : Evidence from Brazil - Bruhn, Miriam; Garber, Gabriel; Koyama, Sergio; Zia, Bilal (World Bank, Washington, DC, 2022)
In 2011, the impact of a comprehensive financial education program was studied through a randomized controlled trial with 892 high schools in six Brazilian states. Using administrative data, this paper follows 16,000 students for the next nine years. The short-term findings were that the treatment students used expensive credit and were behind on payments. By contrast, in the long-term, treatment students were less likely to borrow from expensive sources and to have loans with late payments than control students. Treatment students were also more likely to own microenterprises and less likely to be formally employed than control students.